2014
DOI: 10.1111/jgs.12978
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Activity in Reducing Cognitive Decline in Older Mexican‐American Adults

Abstract: The impact of physical activity on cognitive function in older adults from minority and disadvantaged populations is not well understood. This study examined the longitudinal association between physical activity and cognition in older Mexican Americans. The study methodology included a prospective cohort with longitudinal analysis of data from the Hispanic Established Populations for the Epidemiological Study of the Elderly. General linear mixed models were used to assess the associations and interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Prior research examined the effects of physical activity on cognitive functioning using cognitive assessments [1,4,6,9,11], whereas this study defined cognitive decline as self-reported "difficulty concentrating, remembering, or making decisions. "…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research examined the effects of physical activity on cognitive functioning using cognitive assessments [1,4,6,9,11], whereas this study defined cognitive decline as self-reported "difficulty concentrating, remembering, or making decisions. "…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study examined females ages 55 to 64, whereas most previous research focused on the elderly [1,[6][7][8]12]. The variables in this study were concurrent levels of cognitive decline and physical activity levels at one point in time; therefore, benefits of physical activity for cognitive decline may not be immediate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations